Network as a Condition of the Economic Action - БезруковаОльга Николаевна (Journal of Economic Sociology, 2010)
The purpose of the paper is the analysis of conceptual scheme that is used in network approach. Initially the paper describes the variety of the definitions for the term “network” that combines the wide range of economic and non-economic processes. The main attention is given to the specificity of the sociological approach. Later the key characteristics of the network structures and their types are defined. Further on the author provides his own view on the network nature and their formation mechanism. The author tries to distinguish the peculiarities of the network and institutional structures and the main principles of the network functions. Finally the short description of the empirical results is given which demonstrates the analysis of concrete phenomena form the network approach view. With help of such analysis the author tries to identify the main advantages and disadvantages of the network approach as an independent instrument for the analysis.